Content Analysis of My Next Words Grade 3: An Evaluation Based on Tomlinson's Criteria - Muhammad Rafli; Fauzan Reza Fahlevi; Aldo Saputra; Roshim Ahmad Musyaffa; Akhmad Ali Mirza; Hesty Widiastuty; Zaitun Qamariah (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to evaluate the My Next Words Grade 3 textbook using evaluation criteria developed by Brian Tomlinson, which include impact, readability, usefulness, practicality, localization, and flexibility. Through a qualitative content analysis approach, this study analyzes the suitability of the content of the book to the needs and characteristics of elementary school students. The results showed that the book had a number of strengths, such as an attractive visual presentation and systematic structure of the material, but also found some weaknesses, such as a lack of local context and challenges in readability for some students. This research provides recommendations for the development of textbooks that are more effective and in accordance with modern pedagogical principles and educational contexts in Indonesia. These findings are expected to contribute to teachers, curriculum developers, and textbook writers in improving the quality of English learning materials at the elementary school level.